2015
DOI: 10.1186/1743-0003-12-4
|View full text |Cite
|
Sign up to set email alerts
|

The generation of centripetal force when walking in a circle: insight from the distribution of ground reaction forces recorded by plantar insoles

Abstract: BackgroundTurning involves complex reorientation of the body and is accompanied by asymmetric motion of the lower limbs. We investigated the distribution of the forces under the two feet, and its relation to the trajectory features and body medio-lateral displacement during curved walking.MethodsTwenty-six healthy young participants walked under three different randomized conditions: in a straight line (LIN), in a circular clockwise path and in a circular counter-clockwise path. Both feet were instrumented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
4
26
0
Order By: Relevance
“…Additionally, the stance phase of the inside leg and the swing phase of the outside were increased, both contributing to an increased duty factor for the inside and reduced duty factor of the outside leg. Our results agree with previous publications regarding the decrease in velocity for turning (Courtine and Schieppati, 2003b;Orendurff et al, 2006;Turcato et al, 2015) and the increase in stance time of the inside leg (Turcato et al, 2015). While the participants in this study maintained an almost constant walking frequency throughout all trials, the study by Turcato et al (2015) revealed a significant decrease in stride frequency for turning, which may be due to their more challenging experimental setup (radius of curvature 1.2 m, participants completing three 360 turns).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, the stance phase of the inside leg and the swing phase of the outside were increased, both contributing to an increased duty factor for the inside and reduced duty factor of the outside leg. Our results agree with previous publications regarding the decrease in velocity for turning (Courtine and Schieppati, 2003b;Orendurff et al, 2006;Turcato et al, 2015) and the increase in stance time of the inside leg (Turcato et al, 2015). While the participants in this study maintained an almost constant walking frequency throughout all trials, the study by Turcato et al (2015) revealed a significant decrease in stride frequency for turning, which may be due to their more challenging experimental setup (radius of curvature 1.2 m, participants completing three 360 turns).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have identified and focused on the two main strategies used to navigate sharp turns, namely 'step' and 'spin' turns, which are defined by the change in direction being away from and towards the side of the limb in stance, respectively (Akram et al, 2010;Huxham et al, 2006;Patla et al, 1999;Taylor et al, 2005). Other studies have investigated steady-state turning manoeuvres such as walking circular pathways (Godi et al, 2014;Segal et al, 2008;Turcato et al, 2015); curved trajectories (Courtine and Schieppati, 2003a;Orendurff et al, 2006); and U-Turns (Guldemond et al, 2007;Hase and Stein, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was probably a cause of turning: the body moving towards the inside provided the acceleration required for turning. Another study on curved walking found that the trajectories affected the trunk inclination significantly and the trunk inclined to the inside of the circle during curved walking [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The simple fact of walking is requiring the equilibrium that the central nervous system organizes through the movement of propulsion connected to body rotations. Turning during walking is a complex activity of the head, the trunk, the pelvis and feet reorientated together with adjustments of the body and counteracting the centrifugal acceleration (Turcato et al, 2015). Apparently, the optimization of movements for the better effect in action is a selection of muscle activation based on principle minimization of muscle recruitment, precision and speed of neural calculation.…”
Section: Physicsmentioning
confidence: 99%